The Current State and Challenges of the Global Textile Industry: Key Directions for the Development of Uzbekistan’s Textile Sector - Akramov, Abduvali; Khodzhiev, Mukhsiddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article discusses the current state of the global textile industry, including the volume of textile product manufacturing in developed countries, the size of the European textile market, and issues such as digitalization of the textile industry, sustainability, and the development of advanced technologies. Additionally, it provides insights into the current economic potential of Uzbekistan's textile industry, the domestic and foreign policies being implemented in the sector, and their outcomes, as well as the conditions being created for entrepreneurs in this field within Uzbekistan.